The importance of using the Internet in tourism promotion - لرباع الهادي (Milev Journal of Research and Studies, 2018)
While the internet overshadowed all domains of life, it used became associated with the concept of “success”, This happened in the tourism sector, where access to tourists and attracting the largest number of them, is not only the availability and use of modern information and communication technologies, and promote the tourist destination through the Internet in the light of the modern electronic tourism market. The study aims to highlight the basic concepts of the tourism promotion process, and to review the importance of using the Internet in this process which is the mainstay of tourism, with access to the reality of the use of the Internet in the promotion of tourism in Algeria.